2007
DOI: 10.1007/s11046-007-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 production by high and low virulent strains of Paracoccidioides brasiliensis

Abstract: The production of prostaglandins (PGs) during fungal infections could be an important suppressor factor of host immune response. Host cells are one source of prostaglandin E(2) (PGE(2)); however another potential source of PGE(2) is the fungal pathogen itself. Thus, both host and fungal PGE2 production is theorized to play a role in pathogenesis, being critical for growth of the fungus and to modulate the host immune response. The purpose of this work was to investigate if high and low virulent strains of Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…These data are consistent with our result that PGE2 completely reversed the inhibitory effect of indomethacin on the growth of C. albicans (Table 1). In addition, a study also showed that incubation of Paracoccidioides brasiliensis cultures with indomethacin significantly inhibited the production of PGE2 and fungal viability (Bordon et al 2007), which supports the hypothesis that a COXdependent pathway is involved in PGE2 production. Alem and Douglas (2004) showed that aspirin also inhibits up to 95% of biofilm formation by C. albicans, but prostaglandins diminished this inhibitory effect.…”
Section: Resultssupporting
confidence: 56%
“…These data are consistent with our result that PGE2 completely reversed the inhibitory effect of indomethacin on the growth of C. albicans (Table 1). In addition, a study also showed that incubation of Paracoccidioides brasiliensis cultures with indomethacin significantly inhibited the production of PGE2 and fungal viability (Bordon et al 2007), which supports the hypothesis that a COXdependent pathway is involved in PGE2 production. Alem and Douglas (2004) showed that aspirin also inhibits up to 95% of biofilm formation by C. albicans, but prostaglandins diminished this inhibitory effect.…”
Section: Resultssupporting
confidence: 56%
“…Since then, prostaglandins have been identified in C. neoformans , several pathogenic species of Candida, P. brasiliensis , and several Aspergillus spp. (Noverr et al ., 2002; Tsitsigiannis et al ., 2005a; Bordon et al ., 2007; Biondo et al ., 2010). …”
Section: Fungal Oxygenases and Their Corresponding Oxylipinsmentioning
confidence: 99%
“…The pathogenic dimorphic yeast, Paracoccidioides brasiliensis , also produced prostaglandins from endogenous and exogenous AA [31,32]. The use of COX inhibitors, indomethacin and piroxicam, not only decreased prostaglandin production but also viability of the yeast.…”
Section: Occurrence Of Eicosanoids In Pathogenic Yeastsmentioning
confidence: 99%